Effect of Physiotherapy on Foot Function During Treatment of Hallux Valgus - Asta Samienė; Vaida Berneckė; Aurelija Simavičienė (Lithuanian Sports University, 2019)
Research background. The present final paper presents an analysis of the effects of physiotherapy on foot function when treating the hallux valgus deformity. The research object was the change of the deformity degree of the great toe, foot pain, muscle strength, load distribution in the sole, trajectory of the sole's center of gravity and foot's contact with the movement's surface in different stages of walking after the treatment. Objectives of the research were to analyze scientific literature about the hallux valgus, the concept of foot function and its treatment; determine the changes in the deformity degree of the great toe, pain intensity and muscle strength prior to and after the physical therapy exercises; assess the load distribution in the soles of the respondents, trajectory of the sole's center of gravity and foot's contact with the movement's surface in different stages of walking prior to and after the physiotherapy exercises. Methods. The study was carried out at the Out-Patient Recuperation Center of the Public Institution Šiauliai National Hospital. The computer-aided pedobarographic assessment of the foot was performed by a representative of the Bauerfeind Company at the Manual Medicine Clinic. The study was carried out from December 2013 to April 2014. Twelve respondents afﬂicted with hallux valgus deformity participated in the study. The duration of the exercise sessions was 11 Results. According to the analysis of the research data, the intensity of pain was inﬂuenced by both the exercises and the use of orthopedic supports. However, the pain decreased more after physiotherapy compared to the use of orthopedic supports. The changes in the deformity degree of the great toe and muscle strength were also positively affected by exercises. In EKt group the muscle strength of the tested muscles changed by 1-2 points. In the EO group the muscle strength and the deformity degree of the great toe remained unchanged after the use of orthopedic supports. Following the analysis of the load distribution in the sole, trajectory of the sole's center of gravity and foot's contact with the movement's surface, it became obvious that the physiotherapy had positive a impact on the decrease of load distribution points in different places of the sole and the trajectory of the sole's center of gravity for the respondents in the Conclusion. After the exercises the toe of one patient was aligned properly and the remaining patients were close to achieving proper alignment. Also, the exercises had a positive inﬂuence on the foot's contact with the movement's surface. The EO group did not observe any positive changes after using the orthopedic supports, i.e. the load distribution points, trajectory of the center of gravity and foot's contact with the movement's surface were not altered. Keywords: hallux valgus, foot function, physical therapy.